DYNAMIC ANALYSIS OF CAPITAL MARKETS: A COMPREHENSIVE STUDY ON GLOBAL ECONOMIC SHIFTS AND THEIR IMPLICATIONS FOR INVESTMENT STRATEGIES AND PORTFOLIO PERFORMANCE - Andi Sumarlin K; Kartijo; Eliagus Telaumbanua; Yupiter Mendrofa; Mohamad Khairi Bin Haji Othman (CV. Adiba Aisha Amira, 2025)
This study explores the intricate relationship between global economic shifts and their implications for investment strategies and portfolio performance in a rapidly transforming global economic landscape. Beginning with a historical perspective, the research traces the evolution from traditional to modern portfolio theories, recognizing the pioneering contributions of Harry Markowitz and subsequent theorists like William Sharpe. Emphasis is placed on the adaptability of modern portfolio theories to address challenges presented by dynamic economic environments. Modern Portfolio Theory (MPT) is scrutinized as a pivotal framework that surpasses static diversification strategies. MPT incorporates the risk and return of individual assets and their correlations, facilitating a nuanced and dynamic portfolio construction approach. Enriching this framework are insights from behavioral finance and dynamic asset allocation, providing practical tools for investors to navigate the complexities of rapidly changing economic landscapes. The study delves into risk management strategies tailored for dynamic environments, focusing on the pivotal role of hedging techniques such as options and futures contracts. Dynamic hedging, with its capacity to adjust positions in response to changing market conditions, is highlighted as essential for navigating uncertainties inherent in economic shifts. Diversification strategies emerge as a cornerstone of effective risk management, extending beyond traditional asset classes. The study underscores the importance of modern diversification strategies, encompassing alternative investments like tangible assets, private equity, and hedge funds. This adaptive diversification approach aims to create portfolios resilient to the impacts of specific economic events, fortifying them against localized economic shifts. This research provides valuable insights for informed investment decision-making in the dynamic global economic landscape.